δ13C analysis of bulk organic matter in speleothems using liquid chromatography-isotope ratio mass spectrometry - Blyth, Alison; Shutova, Y.; Smith, C. (Pergamon, 2013)
The determination of δ13C values in speleothems is of considerable importance in palaeoenvironmental research, but has focussed solely on analysis of the carbonate. Here we demonstrate a new method for analysing the δ13C values of organic matter (OM) trapped in speleothems, utilising flow injection liquid chromatography-isotope ratio mass spectrometry (LCIRMS).Developmental analysis using a homogenised speleothem powder showed that the method is robust, with repeated digests and analyses having an average standard deviation of 0.1‰. Dilution tests with samples of 4-23µg total organic carbon (TOC) show relatively small linearity effects, with the overall standard deviation across a peak response range of 1700-9000 mV being 0.2‰.